DESKRIPSI PROSES MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN PEMAHAMAN FAKTUAL DITINJAU DARI TINGKAT EFIKASI DIRI PADA SISWA KELAS VII SMP NEGERI 1 KOTABARU - Radiatul Adawiah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
One factor that determines the success of the students in learning is self-confidence (self-efficacy). Self-efficacy may affect the form of the activities, objectives and efforts of students in solving problems, especially in terms of thinking. Different confidence will lead to a tendency to think different between the students and other students. The purpose of this study was to determine the process of solving problems of Mathematics Based on factual understanding of students. This research is a descriptive qualitative approach. Researchers act as the main instrument guided by test superitem, self-efficacy scale and interview guides valid. Data collected through the provision of testing and verified by interview. Subjects were students of class VII SMP Negeri 1 Kotabaru consisting of four people (two subjects with high efficacy and two subjects with low efficacy). The research process followed the steps of: (a) formulate indicators Understanding of factual (b) to formulate supporting instruments (tests superitem, the scale of self-efficacy, and interview guides) are valid and reliable, (c) making the subject of research by the state of self-efficacy , (d) data collection to reveal the levels of thinking student with test superitem, (e) perform triangulation method to obtain valid data, (f) perform data analysis (g) discussing the results of data analysis, (h) withdrawing the conclusion of research. The results showed: (a) subject to the efficacy of high showed a tendency to think at an abstract level expanded, (b) subject to the low efficacy showed a tendency to think the relational level, (c) subject to the efficacy of high and low show berpikiryang same inclination relative to the tingkatunistruktural, multistruktural, and relational and propensity to think differently on abstract levels expanded. Keywords: Math, factual understanding and self-efficacy